2009
DOI: 10.1002/pmic.200800628
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of the thirteen structurally isomeric quartets of N‐terminal dipeptide motifs in peptides by collision‐induced dissociation

Abstract: N-terminal sequencing of protonated peptides is challenging, since each b(2) ion represents two sequence isomers, e.g., NE and EN. Additionally the occurrence of compositional isomers, such as NE and QD, further increases the number of isomers to four (NE, EN, QD, DQ). This leads to a subset of 13 b(2) ion masses where each value represents four individual species. The b(2) ions within such a quartet are characterized by the same elemental composition. To test the utility of CID for differentiation of isomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…This model accounts for the formation of c 1 ions, but is not able to explain variable signal intensities of the c 1 ion relative to the b 2 ion. In a recent study by our group, the presence of c 1 ions was observed upon fragmentation of peptides containing a Q or N residue in N-terminal position 2 for nine synthetic peptides [6]. We also observed that c 1 ions were constantly accompanied by their complementary high mass fragments, the z max-1 ions.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…This model accounts for the formation of c 1 ions, but is not able to explain variable signal intensities of the c 1 ion relative to the b 2 ion. In a recent study by our group, the presence of c 1 ions was observed upon fragmentation of peptides containing a Q or N residue in N-terminal position 2 for nine synthetic peptides [6]. We also observed that c 1 ions were constantly accompanied by their complementary high mass fragments, the z max-1 ions.…”
Section: Resultsmentioning
confidence: 64%
“…A set of pure compound synthetic peptides (starting with YQ) was used for this three cases, and that the differences in the intensities of the c 1 ion are not related to differing b 2 ion structures, but must have their origin in another process. Such a result indicates a significant impact of a second mechanism of c 1 ion formation as was deduced from the presence of z max-1 ions in an earlier study [6].…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations